Caffeine intake almost always affects physical performance and cognitive processes responsible for awareness - Roberto De Giorgio (Federal Council of Pharmacy, 2023)
Sports foods and supplements can play a significant role in the sports nutrition plans of high-level athletes. It has been found that taking specific dietary supplements can have ergogenic and performance-enhancing effects. Over the past two decades, there have been no major changes in the recommendations for caffeine supplementation. However, scientific knowledge has been significant in recent times, such that the state of the art needs to be updated. This study aims to confirm that caffeine (1,3,7-trimethylxanthine), a substance found in beverages such as coffee, tea and energy drinks, can be both an ergogenic support for individuals engaged in physical activity and an effective cognitive support. In this context, this review outlines the current framework of knowledge. The relationship between the uses and effects of caffeine in power and endurance sports has been demonstrated. In order to achieve and maintain the high levels of performance required in sporting events, planning proper sports diet supplementation can only strengthen and revitalize athletes after strenuous training. Furthermore, the effects of caffeine intake on the state of alertness have been evaluated in the military as well. Significant physical performance, such as marching over rough terrain, sometimes with very heavy loads, may be required during military training and tactical operations. In addition, operational situations with reduced or sleep deprivation may occur.Thus, several studies argue that genetic background, diet, gender identity and hormonal status have a bearing on the absorption, metabolism and physiological and functional effects of caffeine. Regarding the key points - individualized dosages and timing of caffeine intake - it would be desirable to go further with the studies to optimize the effects of caffeine.